A Compilation of the Acts of the Legislature Incorporating the City of Macon, Georgia 60 (S. Rose & Co. 1862). - (:unkn) unknown (My University, 1862)
Ordinance Against Carrying Deadly Weapons: That any white person who shall violate the Statutes of the State of Georgia now in force, relative to carrying about his or her person any deadly weapon mentioned in said Statutes, within the limits of the City of Macon, shall, for each offence, on proof thereof before the Mayor of said city, be fined by said Mayor in a sum of not less than fifty, nor more than one hundred dollars, or imprisoned in the common Jail of Bibb county or the Guard House of said city, for any period not exceeding one month, or both fined and imprisoned as aforesaid, in the discretion of the Mayor. And any slave or free person of color who shall carry about his or her person any deadly weapon of any description-such as are manufactured for purposes of offence or defence-within the limits of said city, shall be punished by whipping and imprisonment in the Guard House of said city, at the discretion of the Mayor-the whipping not to exceed seventy-five lashes, and the imprisonment not to exceed thirty days."
Keywords: CARRY